The extent of consumer awareness on the importance of SIRIM certification mark on the products in the market - Mansor, Nurul Hidayah (2002)
The purpose of this research is to identify the level of consumers’ awareness on the importance of SCM Label appeared on the products in the market. This research is to determine how far the consumers practice in buying the products certified with SCM Label. SIRIM Berhad is a well-known certification body that produces standards and quality to a certain product. The certification is so important that benefits both national development and the consumers’ protection. To date SERIM Berhad has developed 2319 Malaysian Standards, registered 829 companies and organizations to TSO 9001-ISO 9002 level. SIRIM Berhad has also approved 1296 products and 609 companies under The Product Certification Scheme. It is so because SIRIM Berhad provided a wide range of testing services to industry. The Product Certification Scheme is generated under the SIRIM QAS Sdn. Bhd., the wholly owned company subsidized by SIRIM Berhad. This scheme offers a cost-effective alternative in the absence of a national or international standard for the products. In this case, the product can be certified to association or industry standards as well as acceptable consumers’ specifications. The scheme guaranteed the products with the SCM Label, can be trusted in terms of quality and standards for better and safety consumption. In order to analyse the level of consumer awareness, a set of questionnaires have been distributed to 100 respondents who have experienced in consuming the products with SCM Label. From the result analyzed, enable the researcher to identify the end consumers’ taste. The feedback and views from them shows the perspective on SCM Label awareness and its benefits. To make this study meaningful, the researcher limits the scope and coverage of respondents. The area chosen were Shah Alam and Malacca. These two areas were selected because of its difference living background and social status. The vast different of end consumers give various experiences and findings. Based on the facts and findings, the researcher has used cross tabulation testing method to prove the respondents’ behaviors in consuming certain products. The researcher has made the conclusion suggesting SIRIM Berhad to look into its positioning strategies to encourage the end consumers to buy products with the SCM Label attached. Besides that, the company should build a strong relationship between the company and the end consumers. This will help the company to educate the people to be wise enough in purchasing products in the market. Several recommendations have been included in the last chapter of this book for the benefits of SIRIM Berhad.